Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Kantor Kecamatan Solear Kabupaten Tangerang - Stefany Thesalonica Putri; Denies Susanto (PT. Alahyan Publisher Sukabumi, 2026)
The purpose of this study is to examine the effect of work motivation and work environment on employee performance at the Solear District Office, Tangerang Regency. The method used is quantitative. The sampling technique uses saturated sampling with a total of 57 respondents. Data analysis includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis (R2), and hypothesis testing (t-test and F-test). Based on the research results, it is stated that work motivation has a positive and significant effect on employee performance. Likewise, the work environment also has a positive and significant influence on employee performance. Furthermore, work motivation and the work environment simultaneously have a positive and significant effect on employee performance.